P011 TETHERED IBD TOOLS TO SUPPORT PATIENTS AND PROVIDERS IN SHARED DECISION-MAKING AND THERAPY ACCESS. (7th February 2019) - Cross, Raymond; Scherl, Ellen J; Fajardo, Kristina; Weinbaum, Eric D; Greene, Laurence; Eichenbrenner, Paula J; Fraser, Kathleen; Bender, Ali Shipley; Moreo, Kathleen
Abstract: Background: Effective tools are needed to support IBD patients and providers in shared decision-making (SDM) and navigating access to appropriate therapies. We developed and evaluated patient and provider educational online apps that present aligned content designed to close gaps in SDM and timely treatment. Methods: The patient and provider web apps present evidence-based IBD treatment recommendations in visual formats, together with strategies and customizable downloads for applying SDM. The web apps are also designed to help patients/caregivers navigate insurance plans and to optimize providers' clinic processes for addressing managed care requirements. Content pertaining to managed care was vetted by the Academy of Managed Care Pharmacy Foundation. To evaluate the tools, pre- and post-education survey items were embedded within the web apps. The web apps were launched in February 2018 and are hosted at www.ibd.care . Results: The patient and provider IBD web apps have been accessed by 6, 982 and 3, 349 unique users, respectively. The number of respondents to opt-in survey items ranged from 331 to 493 in the provider web app and 56 to 258 in the patient web app. 136 physicians, 69 nurse practitioners, and 288 nurses responded to the provider survey. Among patient web app users, 147 reported a diagnosis of IBD (42% Crohn's disease; 58% ulcerative colitis; 69% female). 65% of patients and 41% of providers reported that they/their patients prefer to be "highly involved" in IBD treatment decisions. 47% and 32% of providers strongly agreed or agreed that using evidence-based IBD care pathways within SDM supports informed treatment decisions. 46% of providers planned to share the apps with their IBD patients. 298 patient web app users created a customized guide to use in SDM with providers. On pre-education surveys, only 17% and 28% of patients rated their understanding of their insurance coverage as high or very high. 30% of patients reported experiencing delays of more than 2 weeks from prescription of biologic therapy to insurance coverage approval. Providers rated their confidence in effectively navigating managed care requirements for IBD therapies as very low (11% pre-education; 4% post-education), low (28% pre; 15% post), moderate (41% pre; 36% post), high (14% pre; 32% post), or very high (6% pre; 13% post). Providers identified actions to improve prior authorization (PA) processes, including adapting interprofessional workflows, protocols, and documentation processes. Conclusions: The web apps present a model for patient and provider education aligned with the principles of SDM, and may be useful to encourage adoption of treatment guidelines in PAs, electronic PAs, and EHR management. Survey findings from patients and providers accessing the web apps can inform educational strategies to close gaps in SDM and patient access to needed therapies.